Evaluation of the use of steel slag in micro surfacing - de Castro, Pedro Bastos; da Silva, Bruno Tiago Angelo; Barroso, Suelly Helena de Araújo (Transportes, 2020)
Micro surfacing (MS) is a type of bituminous coating frequently applied in the surface of pavement structures in order to prevent the occurrence of common distress and/or as a maintenance procedure. Micro surfacing has successfully been used in some states of Brazil as well as in many countries all over the world. Local aggregates used for micro surfacing composition are in some cases scarce and/or expensive. Therefore, the main objective of the present research is to verify the technical, financial and environmental viability of using steel slag aggregate (SSA) in micro surfacing applications. To reach the main objective, a procedure was developed in four steps. In the first step it was made the characterization of conventional (granitic) and alternative aggregates (steel slag) and polymer-modified emulsified asphalt. In the second step, mix design, surface abrasion resistance and setting time tests were performed. In the third step, the micro surfacing mechanical performance was analyzed using a laboratory traffic simulator to observe accumulated permanent deformation; surface wear; micro texture and macro texture. In the fourth step, a comparative study of costs concerning micro surfacing application using conventional mineral aggregate (MS-MA) and alternative aggregates (MS-SSA) were performed. The laboratory procedure results indicated that the steel slag studied has the potential to be used in micro surfacing applications with more rutting resistance and better durability. The cost analysis showed for medium transport distances bigger than 60 km, the MS-SSA will be cheaper than MS-MA solution.